FORMULATION OF NANOPARTICLES OF ANTI-MIGRAINE DRUGS TRIPTANS BY COACERVATION METHOD - A, Farshid; Csr, Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Triptans are effective medicines used to treat migraine and certain other headaches. This study has been conducted to prepared nanoparticles (NPs) of triptans by coacervation technique using a different drug to polymer ratios and evaluated. Methods: Polymers such as albumin and gelatin and cross-linking agent were used at different levels to prepare triptan NPs with high entrapment efficiency (EE) and low particle size (PS). Completion of the reaction was confirmed by infrared spectra. NPs were evaluated for shape and surface morphology, polydispersity index, zeta potential, EE, and PS distribution. Results: Among all the formulation, AA5 formulation of triptan-loaded albumin NPs (ANPs) has small PS and high EE. Conclusion: In this study, we have found that the ANPs in the presence of 4% glutaraldehyde as a cross-linking agent could be used as a delivery vehicle of triptans.